2022
DOI: 10.2807/1560-7917.es.2022.27.4.2001619
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Guillain–Barré syndrome after vaccination against human papillomavirus: a systematic review and meta-analysis, 1 January 2000 to 4 April 2020

Abstract: Background Guillain–Barré syndrome (GBS) is a rare autoimmune disease that can follow viral infections and has in a few cases been linked to vaccinations. Pre-licensure clinical trials did not observe an association between human papillomavirus (HPV) vaccination and GBS, a post-marketing study from 2017 reported an increased relative risk. Aim We assessed the risk of GBS after HPV vaccination through a systematic literature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…A systematic literature review and meta‐analysis of published data is one way to draw unbiased conclusions. A recent meta‐analysis by Boender et al 27 concluded that the risk of Guillain–Barré syndrome after HPV vaccination lacks statistical significance, which had been inconclusive due to the different results among published articles. Scientific evaluations/conclusions based on these approaches would provide appropriate information for healthcare providers, policymakers, and the general public.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic literature review and meta‐analysis of published data is one way to draw unbiased conclusions. A recent meta‐analysis by Boender et al 27 concluded that the risk of Guillain–Barré syndrome after HPV vaccination lacks statistical significance, which had been inconclusive due to the different results among published articles. Scientific evaluations/conclusions based on these approaches would provide appropriate information for healthcare providers, policymakers, and the general public.…”
Section: Discussionmentioning
confidence: 99%
“…While rare, some individuals may experience more serious adverse reactions to the HPV vaccine. These can include severe allergic reactions, fainting, or Guillain-Barré syndrome [ 9 ]. However, these negative effects are incredibly uncommon, and getting vaccinated has many more advantages than disadvantages.…”
Section: Reviewmentioning
confidence: 99%